2016
DOI: 10.1039/c6ra23301e
|View full text |Cite
|
Sign up to set email alerts
|

Few molecule SERS detection using nanolens based plasmonic nanostructure: application to point mutation detection

Abstract: Self-similar chain based nanolens plasmonic devices were fabricated for detecting single point mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The measured Raman peaks of the R6G molecules are mainly located at 1181 cm −1 , 1314 cm −1 , 1365 cm −1 , 1514 cm −1 and 1661 cm −1 . The R6G Raman peak at 1181 cm −1 and 1365 cm −1 are attributed to C-H x in-plane bending and the COO- vibration 33 . Those at 1514 cm −1 , and 1661 cm −1 are related the C-C ring stretching vibration 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured Raman peaks of the R6G molecules are mainly located at 1181 cm −1 , 1314 cm −1 , 1365 cm −1 , 1514 cm −1 and 1661 cm −1 . The R6G Raman peak at 1181 cm −1 and 1365 cm −1 are attributed to C-H x in-plane bending and the COO- vibration 33 . Those at 1514 cm −1 , and 1661 cm −1 are related the C-C ring stretching vibration 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The R6G Raman peak at 1181 cm −1 and 1365 cm −1 are attributed to C-H x in-plane bending and the COO- vibration 33 . Those at 1514 cm −1 , and 1661 cm −1 are related the C-C ring stretching vibration 33 . The Raman peak of LiNbO 3 is only observed at 866 cm −1 , which can be easily separated from the Raman peaks of R6G molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Further work on this field has been performed by Das et al., which extended the initial results of ref. [] to several organic molecules, including Rhodamine 6G and Benzenethiol . They showed that the SERS intensity can be enhanced by considering a device where each nanolens is replaced by an assembly of combined multiple nanolenses, as reported in Figure for devices with a number of nanolenses ranging from one to four.…”
Section: Complex Nanoplasmonic Materials For Integrated and Ultrafastmentioning
confidence: 99%
“…[13] where gold nanolenses obtained by ablation were shown to provide enhancement G SERS ∼ 10 9 . Yet another experimental progress was top-down nanofabrication of various nanolenses with the number of the individual nanospheres ranging between three and eight [54,55]. These nanospheres provided single-molecule or a fewmolecule SERS sensitivity and were used, in particular, to detect point-like mutations in peptides related to the protein encoded by the BRCA1 (breast cancer suppressor) gene [54].…”
Section: Shape Enhancement Of Sers In Nanolensesmentioning
confidence: 99%